Dampak Covid-19 Pada Perekonomian Masyarakat Petani Di Desa Patokaan Kecamatan Talawaan Kabupaten Minahasa Utara - Andilan , Trendy Boy; Mingkid , Elfie; Londa , Very Y. (Sam Ratulangi University, 2023)
The purpose of this study was to determine the Impact of Covid-19 on the Community Economy Especially Farmers in Patokaan Village, Talawaan District, North Minahasa Regency. Data collection techniques are observation and interviews with research informants and documentation studies. The research method is descriptive with data analysis namely data reduction, data presentation and drawing conclusions. The results showed that the impact of the Covid 19 pandemic on the economy of the people in Patokaan Village, Talawaan District, North Minahasa Regency was in the income sector, economic activity, expenditure and community savings. The income of people who work as farmers has decreased due to difficulties selling agricultural products so that the costs incurred are not in accordance with the results obtained, traders who have difficulty finding buyers, private employees who are forced to lay off. Public spending continues to increase for basic needs and the need for medical medicines as well as facing rising prices of basic goods. People cannot save/save but instead use their savings to be able to buy basic necessities whose prices are increasing. The central and regional governments are making various efforts to stimulate the economy with policies providing assistance, be it social assistance, non-cash food assistance, preemployment card policies and subsidies for MSMEs. In order to strengthen the economy of the people in Patokaan Village, the village government is actively helping the community to sell agricultural products to people outside the village and those in Patokaan Village. In addition to channeling assistance through village funds for direct cash assistance to the people of Patokaan Village, Talawaan District, North Minahasa Regency.